METHODS FOR BUILDING A KNOWLEDGE BASE USING ARTIFICIAL INTELLIGENCE (Modern education and development, 2025)
Artificial Intelligence (AI) has made significant strides in various fields, one of the most promising applications being the creation and management of knowledge bases. Knowledge bases are crucial for managing large amounts of data, facilitating quick access to relevant information, and supporting decision-making processes across various domains. This article explores the methods for building and enhancing knowledge bases using AI, focusing on techniques such as machine learning, natural language processing (NLP), and semantic web technologies. By examining AI’s role in automating data extraction, knowledge representation, and reasoning processes, we highlight how AI can make knowledge bases more efficient, accurate, and adaptable. Additionally, the article discusses challenges in AI-driven knowledge base development and the future prospects of intelligent knowledge management systems.